Perbaikkan Strategi Perkuliahan Melalui Pengembangan Perangkat Pembelajaran Elektronika Dasar 1 Di Prodi Pendidikan Fisika FKIP Unri Pekanbaru - Rahmad, M. (Jurnal Pilar Sains, 2008)
The lecturer´s some constraint in Elementary Electronics 1 teaching: student´s electronics basic low,peripheral of less teaching, a few of reference, and less precise method. This matter cause learn result ofstudent relative low of Elementary Electronics 1 in physics education program FKIP UNRI. This Researchpuspose to look for alternative learning strategy to increase result of lecturing of Elementary Electronics 1through repair of peripheral of study. Research procedure divided any three phase: preparation, execution ofaction, and observation, evaluation, reflection. Phase execution of action consist of two cycle: cycle 1 usemethod deliver a lecture and demonstrate while cycle 2 discourse, demonstration, and experiment. Data resultof process learn to teach to be obtained from result of evaluation in the form of tes at cycle I and II withmeasuring indication determined from: 1) improvement of activity student learning of cycle to cycle, 2)reached value of student 85% getting value3 6,5. Research result from repair of peripheral of study withapplying of integrate discourse method, demonstration, and experiment in lecturing of ElementaryElectronics 1 can improve learn result which seen from mean result of tes at cycle 1 that is 73,34 and 80,44 atcycle 2.Key words: learning strategy, demonstration method, experiment method